The Criminal Liability of Commercial Legal Entities in the Current Criminal Code of Vietnam - Hung, Nguyen; Thang, Mai Van; Hanh, Tran Thu (PRAWO i WIĘŹ, 2022)
The criminal liability of commercial legal entities has been established in the criminal laws of many countries around the world. In Vietnam, the Criminal Code approved by the 13th National Assembly of the Socialist Republic of Vietnam on November 27, 2015, officially recognizes the criminal liability of commercial legal entities. This has marked thedevelopment of the country’s criminal law in line with the general trend of criminal law in the world to meet the requirements of the prevention and fight against crime. The addition of provisions on the criminal liability of commercial legal entities is of great significance in tightening the legal corridor in current Vietnamese economic integration. However, the 2015 Criminal Code regulating the criminal liability of commercial legal entities also poses new problems in terms of both the theory and practice of the law’s application. One crucial issue is the proven activity in cases where a commercial legal entity is accused. To clarify the problem of proven activity in such cases, these authors outline and analyse the provisions of the 2015 Criminal Code on the criminal liability of commercial legal entities.